Implikasi Gadget Terhadap Masyarakat Hindu di Bali - Ni Nyoman Sri Widiasih (UHN IGB Sugriwa Denpasar, 2015)
Gadget is one of the successful communication technology products is booming in this millennium century. Gedget allows humans to interact or communicate with another human being without a limited time, place and space. Progress society characterized by the development of science and technology. Science and technology major effect on human life and activity. Positive implications that science and technology can facilitate human in Survival. With the science and technology, human creativity challenged to continue and develop ideas berkualitasnya to be something useful for humans, and the natural surroundings. While the negative implication is that he has now increasingly rely on technology to run his life, so he became a creature lazy, spoiled and less willing to work hard. In reality, not all the problems facing humanity can be solved by technology. The function of religion as a human guide in these conditions is very important. Hinduism is not anti to the technology, it Hindu suggest the importance of building a strong civilization. Hinduism has given life provision and guidelines long before humans evolved in advanced age as it is today. The concept of Tri Pramana and Wiweka should remain aware and understood in Survival.